Time to rethink the teacher-family alliance? Central issues in the "pandemic" literature on home-school cooperation - Paola Dusi; Audrey Addi-Raccah (University of Bologna, 2022)
COVID-19 added a new dimension to the relationship between school professionals and students' families: a virtual one. To explore this shift and the associated challenges, we performed a bibliometric analysis of research literature published on the topic to the end of 2021. Our guiding question was: what kind of themes are emerging in literature on the school-family relationship in association with COVID-19? Our search of Scopus, Web of Sciences and ERIC retrieved 286 articles. Using VOSviewer, we conducted a bibliometric analysis based on article keywords to map the field, producing a visual representation of networks of themes. Four clusters emerged: "educational players", "distance learning", "partnership" and "social context". Unsurprisingly, the analysis suggests a shift in the roles of parents and teachers, with the digital sphere becoming central to their relationship. Beyond this, the crisis has cast light on both existing problems and the potential of a partnership based on a genuine sharing of responsibility.